Rectovaginal Fistulae in Post Repair Chronic Perineal Rupture: Fistula Rektovagina pada Pascarepair Ruptur Total Perienum Lama - Budi I. Santoso; Shirley A. Tunggadewi; Yulia M. Sari (Indonesian Journal of Obstetrics and Gynecology, 2021)
Objective: To report and discuss the causes and management of rectovaginal fistula in post repair chronic total perineal rupture.Method: A case report, a 29-year-old female patient who came to Fatmawati General Hospital with complaints of anal incontinence 9 days after repair chronic total perineal rupture. Rectovaginal examination revealed a rectovaginal fistula 2 mm in diameter at 1.5 cm proximal to the hymenal ring.Discussion: Rectovaginal fistula is one of the complications after repair of hronic total perineal rupture which disturbs the quality of life of women. The patient was diagnosed with a rectovaginal fistula in post repair chronic total perineal rupture. Conservative management with wound care and administration of honey to the patient showed improved postoperative outcome.Conclusion: Anatomical identification of the anal sphincter complex, surgical technique and postoperative care are important in preventing complications following repair of chronic total perineal rupture repair.Keywords : obstetrics sphincter anal injury, postrepair chronic, rectovaginal fistulae . Abstrak Tujuan : Untuk melaporkan dan mendiskusikan penyebab dan tatalaksana kasus fistula rektovagina pasca repair ruptur perineum total lama.Metode: Sebuah laporan kasus, pasien perempuan 29 tahun yang datang ke RSUP Fatmawati dengan keluhan inkontinensia anal 9 hari pascarepair ruptur perineum total lama. Pemeriksaan rectovaginal menunjukkan fistula rektovagina diameter 2 mm pada 1,5 cm proksimal hymenal ring.Diskusi : Fistula rektovagina merupakan salah satu komplikasi pascarepair ruptur perineum total yang mengganggu kualitas hidup perempuan. Pasien didiagnsos fistula rektovagina pascarepair ruptur perineum total lama. Manajemen konservatif dengan perawatan luka dan pemberian madu pada pasien menunjukkan perbaikan luaran paska operasi.Kesimpulan: Identifikasi anatomis kompleks sfingter ani, teknik operasi dan perawatan pascaoperasi penting dalam mencegah komplikasi pascarepair ruptur perineum total lama.Kata kunci: cedera sfingter ani obstetri, fistula rectovagina, repair ruptur perineum total lama